AL-THULATHIYYAT DALAM KITAB INDUK HADITH - Kudhori, Muhammad (IAIN Kediri, 2017)
One of privilege of Islam brought by the Prophet Muhammad SAW is the existence of news linker to the followers. The news linker (riwayah) is sanad. The sanad condition in Islam gets serious attention from hadith experts. In the sanad hadith field, there is one kind of sanad that is prioritized than the others. It is happened when they face a contradictive condition between two contradictive hadith. The sanad is al-sanad al-Ã¢â‚¬ËœÃ„â‚¬lÃ„Â« namely a sanad hadith that consists of minimum linkers (riwayah). The importance of this sanad is for the importance of the sanad heigth and supporting factor to make easier in checking the linkers (riwayah). From al-sanad al-Ã¢â‚¬ËœÃ„â‚¬li type, there is sanad form that the linkers (riwayah) are only three people known as thulÃ„ÂthiyyÃ„Ât terms. Some Hadith that have sanad Ã¢â‚¬ËœÃ„ÂlÃ„Â« or hadith thulÃ„ÂthiyyÃ„Ât do not always have valid (sahih) quality, since the validity analysis of hadith depends only on five validity (sahih) requirements that have been set by hadith experts. Hadith thulÃ„ÂthiyyÃ„Ât will have high value when it is supported by valid (sahih) hadith quality. Keywords: hadith, sanad, sanad Ã¢â‚¬ËœÃ„ÂlÃ„Â«, thulÃ„ÂthiyyÃ„Ât